Major regional differences in Automated External Defibrillator placement and Basic Life Support training in France: Further needs for coordinated implementation. (September 2017) - Karam, Nicole; Narayanan, Kumar; Bougouin, Wulfran; Benameur, Nordine; Beganton, Frankie; Jost, Daniel; Lamhaut, Lionel; Perier, Marie-Cécile; Cariou, Alain; Celermajer, David S.; Marijon, Eloi; Jouven, Xavier
Abstract: Background: Public Access Defibrillation (PAD) programs have emerged since mid-1990s with the aim of improving survival from Out-of-Hospital Cardiac Arrest (OHCA). The extent to which their implementation in the community differs among different areas has not been evaluated. Methods: We carried out a 5-year prospective national evaluation of PAD programs in 51 French districts (29.3 million inhabitants), through the cumulative density of Automated External Defibrillator (AEDs) and the proportion of persons educated in Basic Life Support (BLS). Results: Major regional discrepancies were observed with AED density from 5 to 3399 per 100, 000 inhabitants per 1000 km 2, and BLS-educated inhabitants varying from 6955 to 36, 636 per 100, 000 inhabitants. Only 18 districts (35.3%) achieved both AED density and educational rate above median (>13, 988 and >22, respectively). Extrapolating the data from the French national registry on sports OHCA, mean survival rate was two-folds higher with AED density above the median (7.9% vs. 17.8%, P <  0.001) and four-fold higher with BLS-education above the median (5.0% vs. 20.9%, P <  0.001). In the group with both AED density and BLS-education level above the median, the survival rate reached up to 22.5%. Only the rate of population BLS education remained independently associated with survival (OR 1.64, 95% Confidence Interval 1.17–2.31; P  = 0.0045). Conclusions: Major heterogeneities in PAD programs exist, with significant room for better coordination in implementation. Population education in BLS provides an important benefit, regardless of the density of AEDs deployed, which should be taken into account in planning public health policies for improving OHCA survival.